Augmented Reality for Teaching Storytelling in a Rural Foundation Phase Primary School: Integrating a Place-Based Approach - Pretty Thandiswa Mpiti; Bulelwa Makena; Motsi Qoyi (Research in Social Sciences and Technology- OpenED Network, 2023)
Augmented reality (AR) has recently become a new leading edge in mobile-assisted language learning attributed to the popularity of smartphones. The place-based approach (PBA) is a situated, context-rich teaching and learning modality characterized by its relationship to place. AR and PBA have proven to be useful in educational settings; however, few studies have observed them being used jointly. This study aims to explore the combination of AR and PBA in teaching storytelling in a foundation phase (FP) rural primary school. Based on current trends, the study also aims to design learning principles for teaching that will help language teachers integrate this innovative technology and approach into literacy teaching. The study was tested with two FP teachers and 12 FP learners in a real classroom and carried out with qualitative observations and semi-structured interviews. The findings reveal that learners are more motivated and interested in activities that have been enhanced because they encourage problem-solving, discovery, and socialization. The findings also suggest that technological interventions, particularly when learners work as a team, may have a bigger impact than non-technology-integrated instruction. These results offer demonstrable support for technology use and have useful results for future practice.